LEGITIMASI PUTUSAN PENGADILAN INDONESIA SEBAGAI SUMBER HUKUM MAHKAMAH INTERNASIONAL DALAM PEMBENTUKAN HUKUM INTERNASIONAL - Eka An Aqimuddin (Ikatan Hakim Indonesia (IKAHI), 2023)
Most research has focused on how Indonesian courts apply international law. In fact, Indonesian courts can also help shape international law through the International Court of Justice (ICJ) as a source of law used by the ICJ. This article addresses two main questions about whether or not ICJ could use Indonesian court decisions as a source of international law. The first issue is that the ICJ participated in making international law. The ICJ's decision may come from the domestic court decision. Second, Indonesian court decisions could be used by ICJ as a source of law when making international law. The way to do this is through informal channels, such as legitimacy, which is gained when other countries recognize the decisions of Indonesian courts. Legitimacy can be achieved by improving the system and structure of judicial institutions, creating references to Indonesian court decisions in international languages, assuring judges know both customary law and international law, and encouraging Indonesian judges to become judges in ICJ.